2013
DOI: 10.1530/eje-12-0836
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of a large series of patients with type 1 gastric carcinoid tumors: data from a multicenter study

Abstract: Objective: To study the clinical presentation, diagnostic approach, response to treatment, and the presence of other pathologies in patients with gastric carcinoid type 1 (GC 1) tumors. Design and methods: Retrospective analysis of 111 patients from four institutions and a mean follow-up of 76 months. Results: The main indications for gastroscopy were upper gastrointestinal tract symptoms. The mean number of lesions, maximum tumoral diameter, and percentage of cells expressing Ki-67 labeling index were 3.6G3.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 38 publications
2
87
0
5
Order By: Relevance
“…28,29 Limited studies, including a few small prospective studies, have demonstrated regression or complete disappearance of tumors and marked decrease in serum gastrin, lasting up to several years. [30][31][32][33][34][35][36][37][38][39] SSAs (e.g. octreotide and lanreotide) can be considered in cases in which endoscopic resection is not feasible due to extensive multifocal disease, or submucosal/lymph node involvement, as well as recurrent disease after repeated endoscopic resection.…”
Section: Medical Managementmentioning
confidence: 99%
“…28,29 Limited studies, including a few small prospective studies, have demonstrated regression or complete disappearance of tumors and marked decrease in serum gastrin, lasting up to several years. [30][31][32][33][34][35][36][37][38][39] SSAs (e.g. octreotide and lanreotide) can be considered in cases in which endoscopic resection is not feasible due to extensive multifocal disease, or submucosal/lymph node involvement, as well as recurrent disease after repeated endoscopic resection.…”
Section: Medical Managementmentioning
confidence: 99%
“…In well-differentiated neoplasms less than 1 cm, only observation and control endoscopy every 12 months is possible [52], or endoscopic excision [10]. In well-differentiated neoplasms larger than 1 cm, in EUS test not invading the muscularis propria, endoscopic mucosal dissection (ESD) is the preferred method [53].…”
Section: Gastric Neuroendocrine Tumours (Type 1-3)mentioning
confidence: 99%
“…In this series, index cases 1-5 and 7-9 (Table 1) were of Type I which usually accounts for 70% -80% of gastric NET cases. They are small multifocal lesions (median diameter of 5 mm) associated with autoimmune chronic atrophic gastritis, due to gastric achlorhydria-hypergastrinemiaenterochromaffin cell hyperplasia/ tumour mechanism [5,6,8,18] They occur mostly in women and are usually nonfunctioning tumors, typically found during UGI endoscopy performed for dyspepsia or for macrocytic or iron deficiency anemia They are usually benign and well differentiated (NET G1), however, rare cases of metastatic spread and bad prognosis have been described [13]. Index case 4 ( Figures 1a, 1b, 1c) small polyp on OGD with haematoxylin/ eosin and synaptophysin markers on histology respectively while index case 8 ( Figure 2) shows an umbilicated lesion.…”
Section: Open Accessmentioning
confidence: 99%
“…Being usually well differentiated and with low Ki67 (NET G1), generally have an excellent prognosis. Five year survival rates are >95% but they have an indolent clinical course with a median recurrence-free survival of 24 months [5,18,22,23]. Guidelines for post treatment surveillance from the National Comprehensive Cancer Network NCCN, the North American Neuroendocrine Tumour Society (NANETS) and the European Neuroendocrine Tumour Society (ENETS) of Type I and II gastric carcinoids ≤2 cm include history and physical examination with 6 to 12 monthly upper endoscopy for three years and annually thereafter.…”
Section: Open Accessmentioning
confidence: 99%